Cheating time science, sex, and aging - Gosden, Roger (Macmillan, 1996)
While laboratory and clinical medicine strive to stave off the problems of ageing, today's media-dominated society demands that we not only feel good but look good. This book is written for anyone who is curious about the ageing of their body. It explains what ageing is, who ages and who is "immortal" - and how and why - so that the range of age changes in the body may be appreciated. In it, the author explores the realms of reproductive biology and examines the curious trade-off between our reproductive capacity and our lifespan, showing how crucial the sex hormones are to our general youthfulness and well-being. He also explains how the decay of living cells is not fixed by the laws of physics but is affected by the same forces that have shaped our bodies, thus introducing the possibility of change, of stopping the tide of decay and decrepitude.